Penggunaan Bahasa Jurnalistik pada Headline Surat Kabar Tribun Lampung - Abiyan Rafi Rahmanda (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study aims to describe how the use of journalistic language in the Headline of Lampung Tribune Newspaper. Where in a mass media it is important to present news whose language uses journalistic language to ensure that the information conveyed can be conveyed clearly and there is no misinterpretation in reading a news. The method used is descriptive qualitative method with Lampung Tribune Newspaper Headline as the object of study. The data collection technique is a literature study on journals or documents related to Journalistic Language. The results of this study show that the Lampung Tribune Newspaper Headline in presenting the news has used appropriate journalistic language. It's just that of course there are a few shortcomings where there are some news that contain technical language or foreign words that may not be familiar to many people.